Paradigm change at all levels - Abd. Rahman, Nordin; Amat@Halimi, Mahani; Hashim, Siti Hasshura; Harun, Rostam (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
When we discuss about change, especially within the agricultural and entrepreneurial extension the focus has mainly been pointing towards the farmers or the receiving end. Yes, that is the target audience. However, in many situations some of the unsuccessful agricultural programmes or projects were not within the controls of farmers of agro entrepreneurs. Agricultural projects success depended on many outside influencing factors. Agricultural project management is one crucial factor that determines the success or failures of agricultural and agro entrepreneurial extension. This issue therefore must be address seriously in order to ensure the extension programmes benefit the targeted audience and become a success.